A mutation within the SH2 domain of slp-76 regulates the tissue distribution and cytokine production of iNKT cells in mice - Danzer, Claudia Agnes; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al. (European Journal of Immunology, 2016)
TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp-76 on iNKT-cell biology. Compared to B6 controls, slp-76(ace/ace) mice carrying a missense mutation (Thr428Ile) within the SH2-domain of slp-76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP-deficient mice. Like ADAP(-/-) iNKT cells, slp-76(ace/ace) iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate-early gene Nur77 and a decreased adhesion to ICAM-1. Furthermore, CD11b-intrinsic effects inhibited cytokine release, concanavalin A-mediated inflammation, and iNKT-cell accumulation in the liver. Unlike B6 and ADAP(-/-) mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP-1-expression was enhanced in slp-76(ace/ace) mice. Blockade of NP-1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP-1 as an iNKT-cell-specific adhesion factor. Thus, slp-76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP-dependent and -independent mechanisms.
EVALuna2:2050